Alpine altitude climate treatment for severe and uncontrolled asthma: An EAACI position paper. Issue 7 (15th February 2022) - Fieten, Karin B.; Drijver‐Messelink, Marieke T.; Cogo, Annalisa; Charpin, Denis; Sokolowska, Milena; Agache, Ioana; Taborda‐Barata, Luís Manuel; Eguiluz‐Gracia, Ibon; Braunstahl, Gerrit J.; Seys, Sven F.; van den Berge, Maarten; Bloch, Konrad E.; et al.
Abstract: Currently available European Alpine Altitude Climate Treatment (AACT) programs combine the physical characteristics of altitude with the avoidance of environmental triggers in the alpine climate and a personalized multidisciplinary pulmonary rehabilitation approach. The reduced barometric pressure, oxygen pressure, and air density, the relatively low temperature and humidity, and the increased UV radiation at moderate altitude induce several physiological and immunological adaptation responses. The environmental characteristics of the alpine climate include reduced aeroallergens such as house dust mites (HDM), pollen, fungi, and less air pollution. These combined factors seem to have immunomodulatory effects controlling pathogenic inflammatory responses and favoring less neuro‐immune stress in patients with different asthma phenotypes. The extensive multidisciplinary treatment program may further contribute to the observed clinical improvement by AACT in asthma control and quality of life, fewer exacerbations and hospitalizations, reduced need for oral corticosteroids (OCS), improved lung function, decreased airway hyperresponsiveness (AHR), improved exercise tolerance, and improved sinonasal outcomes. Based on observational studies and expert opinion, AACT represents a valuable therapy for those patients irrespective of their asthma phenotype, who cannot achieve optimal control of their complex condition despite all the advances in medical science and treatment according to guidelines, and therefore run the risk of falling into a downward spiral of loss of physical and mental health. In the light of the observed rapid decrease in inflammation and immunomodulatory effects, AACT can be considered as a natural treatment that targets biological pathways. Abstract :